2007
DOI: 10.1016/j.carbon.2006.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fiber from natural biopolymer Bombyx mori silk fibroin with iodine treatment

Abstract: Carbon fibers were prepared from silk fibers after an iodine treatment and the carbon yield, fiber morphology, structure and mechanical properties were investigated.A single or multi step carbonization process was used for the preparation. In the single step process, silk fibroin (SF) fibers were heated from 25 to 800 °C with a heating rate of 5 °C min-1 under Ar atmosphere. However, the carbon fiber obtained was partially melted and was too fragile to handle. For better performance, SF fibers were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…Figure 1 shows Raman spectrum of pristine SWCNTs. The bands were observed at 1341 cm -1 (D band) and 1592 cm -1 (G band), corresponding to amorphous carbon impurities and carbon nanotubes, respectively [17]. The band intensity at 1341 cm -1 was extremely low, while the G-band had much higher intensity.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 1 shows Raman spectrum of pristine SWCNTs. The bands were observed at 1341 cm -1 (D band) and 1592 cm -1 (G band), corresponding to amorphous carbon impurities and carbon nanotubes, respectively [17]. The band intensity at 1341 cm -1 was extremely low, while the G-band had much higher intensity.…”
Section: Resultsmentioning
confidence: 97%
“…19,20 The use of iodine treatment to increase the carbon yield has also been extended to biobased precursors, such as silk broin. 21 In other work, sulphuric acid treatment of cellulosic bre has been shown to increase the carbon yield by 300%.…”
Section: 18mentioning
confidence: 99%
“…Under identical conditions and in the same line of investigation as in [116], Kahn et al [118] studied the carbon formation from Antheraea pernyi silk fibroin fiber. The composition of the latter silk is different from that of B. mori silk, having predominantly alanine (Ala), aspartic acid (Asp), and arginine (Arg) amino acid residues.…”
Section: Iodine-proteinic Fiber Complexesmentioning
confidence: 99%
“…Shao and his coworkers [115] treated a degummed and UV/ozone irradiated B. mori silk fiber with saturated iodine ethanolic solution in the dark at 22°C for 24 h. The content of iodine was about 5% in the bulk iodinated silk and 0.9% on the surface. Khan et al [116] reported a process of making carbon fiber from B. mori silk fibroin after iodine treatment. The silk fibroin was exposed to iodine vapors at 100°C for varying periods of time, after which the fiber color turned to dark brown.…”
Section: Iodine-proteinic Fiber Complexesmentioning
confidence: 99%